2004
DOI: 10.1002/app.13576
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of i‐PP shear‐induced crystallization layers developed in a slit die

Abstract: ABSTRACT:In this work, the shear-induced crystalline layers of isotactic polypropylene (i-PP), developed in a slit die, were characterized by different techniques. Rheological studies made in a strain-controlled rheometer, at different crystallization temperatures, T c , allowed us to observe that the induction time for the beginning of the shear-induced crystallization, t i , decreased as the shear rate increased, whereas at a given shear rate, the higher the T c , the higher the t i . The thickness of the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 19 publications
7
23
1
3
Order By: Relevance
“…If no high pressure were applied, the increase in Q would increase the shear rate and therefore would decrease the time for the beginning of the flow induced crystallization as already confirmed in our labs [2]. However, during the injection molding packing stage, a high pressure is applied and crystallization occurs under the influence of this high pressure.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…If no high pressure were applied, the increase in Q would increase the shear rate and therefore would decrease the time for the beginning of the flow induced crystallization as already confirmed in our labs [2]. However, during the injection molding packing stage, a high pressure is applied and crystallization occurs under the influence of this high pressure.…”
Section: Resultssupporting
confidence: 64%
“…During processing, a polymer is subjected to high gradients of temperature, pressure, and deformation rates. Therefore, its morphology and crystallization kinetics under quiescent conditions will be different from that under processing conditions [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presence of flow, it is observed 12 that the i-PP chains orient, creating fibrillar nucleus. It has also be shown 1 that the quantity of β phase in i-PP samples processed in a slit die decrease with the decreasing of the shear rate imposed during the crystallization process;…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the developed morphology reflects these flow patterns, and usually is composed of different and characteristic layers along the thickness of the sample [1][2][3][4][5][6][7][8][9] . In the case of semi crystalline thermoplastics with fast crystallization kinetics, this morphology is known as "skin-core" and is formed by three main zones [4][5][6][10][11][12][13][14][15][16] :…”
Section: Introductionmentioning
confidence: 99%
“…It is a well known fact that there are some crystal types of PP with different crystal systems, and surface roughness of BOPP films has been investigated in association with crystal types [2][3][4][5][6][7][8] . Many basic studies have been reported on the formation of α and β crystals [9][10][11][12][13][14] . Natta and Corradini reported in their report in 1960 that unit lattice of α crystal is the monoclinic system, and now it is known as being the most dominant crystal in PP 9) .…”
Section: Introductionmentioning
confidence: 99%